2017
DOI: 10.3928/24748307-20170427-02
|View full text |Cite
|
Sign up to set email alerts
|

Health and Functional Literacy in Physical Rehabilitation Patients

Abstract: Background: People with disabilities, who face multiple barriers to care, experience health disparities, yet few studies have measured health literacy in this population. Objective: This study evaluated functional literacy, health literacy, fluid cognitive function, and self-reported health in people who live in community dwellings with spinal cord injury, stroke, or traumatic brain injury. Methods: Participants with a traumatic spinal cord i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 51 publications
(64 reference statements)
1
26
0
1
Order By: Relevance
“…Further, low HL was associated with poor understanding of injuries and treatment provided, leading to decreased adherence with discharge instructions and longer recovery time [ 7 ]. Hahn et al [ 8 ] showed that among people with spinal cord injury, stroke, or traumatic brain injury; higher HL was significantly associated with better overall health. Additionally, a single study of individuals with spinal cord injuries indicated that lower HL was associated with poorer physical mobility [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, low HL was associated with poor understanding of injuries and treatment provided, leading to decreased adherence with discharge instructions and longer recovery time [ 7 ]. Hahn et al [ 8 ] showed that among people with spinal cord injury, stroke, or traumatic brain injury; higher HL was significantly associated with better overall health. Additionally, a single study of individuals with spinal cord injuries indicated that lower HL was associated with poorer physical mobility [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these studies should unravel the influence of SIL on different social insurance related outcomes, such as received work disability benefits and perceived system justice. This is important because we know limited HL has a negative impact on multiple outcomes, such as active participation in the treatment [ 28 ] and mobility during rehabilitation from physical injuries [ 29 , 30 ]. Additionally, it is important to learn more about the role of professionals in their contact with people with limited SIL, for example if they are able to tailor their communication, and to develop and test interventions targeting clients and professionals in social insurance systems to optimize support of people with limited SIL.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of HRQOL, two systematic reviews identified only four studies that measured both HRQOL and health literacy, with some reporting associations between health literacy and HRQOL, and others not finding such associations (Berkman et al, 2004(Berkman et al, , 2011. As the field of health literacy has advanced, more studies in diverse populations are emerging to investigate the associations between health literacy and HRQOL; these results have also been mixed (Hahn et al, 2015(Hahn et al, , 2017; This document is copyrighted by the American Psychological Association or one of its allied publishers. This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of HRQOL, two systematic reviews identified only four studies that measured both HRQOL and health literacy, with some reporting associations between health literacy and HRQOL, and others not finding such associations (Berkman et al, 2004, 2011). As the field of health literacy has advanced, more studies in diverse populations are emerging to investigate the associations between health literacy and HRQOL; these results have also been mixed (Hahn et al, 2015, 2017; Montbleau, King, Henault, & Magnani, 2017; Stellefson et al, 2019; Wang, Kane, Xu, & Meng, 2015; Zhang, Li, Fong, & Thumboo, 2009). Because HRQOL is a multidimensional concept, with dozens of disease-specific and generic domains, more research is needed to identify patterns of associations between health literacy and various HRQOL domains.…”
Section: Discussionmentioning
confidence: 99%